2012
DOI: 10.1097/ta.0b013e31826fc928
|View full text |Cite
|
Sign up to set email alerts
|

The lost to trauma patient follow-up

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 5 publications
4
53
0
1
Order By: Relevance
“…Moreover, we found that poor follow-up compliance persisted across much of the demographic subgroups with no one subgroup having a compliance follow-up rate greater than 41%. This disquieting compliance rate is significantly lower than the 60% compliance rate required for trauma outcomes research as suggested in the study by Leukhardt et al 8 In a recent study, Aaland et al 14 reported an impressive 79.3% trauma clinic compliance rate and challenged the belief that trauma patients are noncompliant with follow-up. However, the Aaland et al 14 study was conducted at a Level II trauma center in a suburban community, whereas the present study is set in a population dense urban area with more than five times the population size of the study setting of Aaland et al 14 Moreover, the study of Aaland et al 14 did not specifically look at race and insurance status.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, we found that poor follow-up compliance persisted across much of the demographic subgroups with no one subgroup having a compliance follow-up rate greater than 41%. This disquieting compliance rate is significantly lower than the 60% compliance rate required for trauma outcomes research as suggested in the study by Leukhardt et al 8 In a recent study, Aaland et al 14 reported an impressive 79.3% trauma clinic compliance rate and challenged the belief that trauma patients are noncompliant with follow-up. However, the Aaland et al 14 study was conducted at a Level II trauma center in a suburban community, whereas the present study is set in a population dense urban area with more than five times the population size of the study setting of Aaland et al 14 Moreover, the study of Aaland et al 14 did not specifically look at race and insurance status.…”
Section: Discussionmentioning
confidence: 91%
“…Fisker et al [34], Joe et al [35], and Hu et al [36] reported similar observations to those in the present study. There are few studies with postoperative follow-up in trauma patients [37][38][39]. We had a follow-up of 62% of patients at the end of three months, and patients reported good pain relief and PSS.…”
Section: Discussionmentioning
confidence: 98%
“…the trauma population is demonstrated by our lost to followup rate of 22.2%, higher than previously reported rates of 10.8%. 9 Despite our dedicated LCS, previously suggested as a targeted patient-retention strategy, 2,10 further strategies are needed.…”
Section: Discussionmentioning
confidence: 99%